Respuestas

2012-09-26T23:59:37+02:00

espero que sirva \m/

 

funciones cuadraticas de -5 hasta 5

 

f(x)=9(x)7          

f(-5)=-9(-5)-7

=45-7

=-52

 

f(x)=9(x)7

f(-4)=9(-4)-7

=36-7

=-43

 

f(x)=9(x)7

f(-3)=9(-3)-7

=27-7

=-34

 

f(x)=9(x)7

f(-2)=9(-2)-7

=18-7

=-25

 

f(x)=9(x)7

f(-1)=9(-1)-7

=9-7

=-16

 

f(x)=9(x)7

f(0)=9(0)-7

=0-7

=-7

 

f(x)=9(x)7

f(1)=9(1)7

=9+7

=2

 

f(x)=9(x)7

f(2)=9(2)-7

=18+7

=11

 

f(x)=9(x)7

f(3)=9(3)7

=27+7

=20

 

f(x)=9(x)7

f(4)=9(4)7

=36+7

=29

 

f(x)=9(x)7

f(5)=9(5)-7

=45+7

=38